2005
DOI: 10.1093/jn/135.9.2236
|View full text |Cite
|
Sign up to set email alerts
|

Grain Sorghum Lipid Extract Reduces Cholesterol Absorption and Plasma Non-HDL Cholesterol Concentration in Hamsters

Abstract: Grain sorghum is a rich source of phytochemicals that could potentially benefit human health. In this study, male hamsters were fed AIN-93M diets supplemented with a hexane-extractable lipid fraction from grain sorghum whole kernels. The grain sorghum lipids (GSL) comprised 0.0, 0.5, 1.0, or 5.0% of the diet by weight. After 4 wk, dietary GSL significantly reduced plasma non-HDL cholesterol concentration in a dose-dependent manner with reductions of 18, 36, and 69% in hamsters fed 0.5, 1.0, and 5.0% GSL, respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
64
0
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(70 citation statements)
references
References 38 publications
2
64
0
4
Order By: Relevance
“…This effect was repeated in another hamster model of hypercholesterolemia, when grain sorghum lipid extract included in the diet significantly reduced plasma non-HDL and liver esterified cholesterol levels while increasing HDL levels. (77) In all these studies, total cholesterol levels were reduced in animals consuming sorghum-based diets compared to sorghum-free control diets. In a single negative finding, Lee et al (169) found that while sorghum consumption increased HDL-cholesterol levels, total cholesterol and LDL-cholesterol levels were increased in a rat model.…”
Section: Effects On Serum Lipidsmentioning
confidence: 94%
See 3 more Smart Citations
“…This effect was repeated in another hamster model of hypercholesterolemia, when grain sorghum lipid extract included in the diet significantly reduced plasma non-HDL and liver esterified cholesterol levels while increasing HDL levels. (77) In all these studies, total cholesterol levels were reduced in animals consuming sorghum-based diets compared to sorghum-free control diets. In a single negative finding, Lee et al (169) found that while sorghum consumption increased HDL-cholesterol levels, total cholesterol and LDL-cholesterol levels were increased in a rat model.…”
Section: Effects On Serum Lipidsmentioning
confidence: 94%
“…Based on research in hamsters, Carr et al (77) suggested that the primary cholesterol-lowering mechanism of sorghum lipid extracts appears to be a reduction in cholesterol absorption with a concomitant increase in fecal sterol excretion. Specifically, policosanols (a mixture of longchained primary alcohols) in the sorghum lipid extracts appear to inhibit endogenous cholesterol synthesis.…”
Section: Lipidsmentioning
confidence: 99%
See 2 more Smart Citations
“…(Shakoor et al, 2014) O sorgo destaca-se atualmente como o quinto cereal de maior produção no mundo, sendo uma alternativa ao consumo de cereais convencionais como arroz, milho, trigo e cevada. Como alimento, o sorgo apresenta vantagens devido à elevadas concentrações de compostos fenólicos que atuam como antioxidantes, contribuindo na redução de doenças cardiovasculares (Carr et al, 2005), diabetes (Lakshmi & Vimala, 1996), obesidade (Al-Mamary et al, 2001) e câncer Yang et al, 2009), além de apresentar grande quantidade de fibras alimentares, agregando valor nutricional (Awika et al, 2005). Ademais, o sorgo apresenta alta resistência ao estresse hídrico, respondendo de maneira mais eficiente ao cultivo sob essas condições quando comparado a outros cereais (Magalhães et al, 2000).…”
Section: Introductionunclassified